2021
DOI: 10.1002/ygh2.489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholecystectomy on bile acid diarrhoea biomarkers: A prospective clinical study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Also, although not following a low‐fat diet was a predictor for diarrhoea at 1 week postlaparoscopic cholecystectomy, this was not the case at 3 months. Furthermore, diarrhoea after cholecystectomy may not be due to excessive colonic bile acid exposure 58 . It is also possible that, in this cohort, chronic diarrhoea could be an as yet undiagnosed condition such as coeliac disease, microscopic colitis, post radiation diarrhoea, small bowel overgrowth, lactose intolerance or fat malabsorption 59 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, although not following a low‐fat diet was a predictor for diarrhoea at 1 week postlaparoscopic cholecystectomy, this was not the case at 3 months. Furthermore, diarrhoea after cholecystectomy may not be due to excessive colonic bile acid exposure 58 . It is also possible that, in this cohort, chronic diarrhoea could be an as yet undiagnosed condition such as coeliac disease, microscopic colitis, post radiation diarrhoea, small bowel overgrowth, lactose intolerance or fat malabsorption 59 .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, diarrhoea after cholecystectomy may not be due to excessive colonic bile acid exposure. 58 It is also possible that, in this cohort, chronic diarrhoea could be an as yet undiagnosed condition such as coeliac disease, microscopic colitis, post radiation diarrhoea, small bowel overgrowth, lactose intolerance or fat malabsorption. 59 Because a diagnosis of BAD in the UK necessitates specialist review, 59 and BAD is confirmed by response to bile acid sequestrant medication, this is unlikely.…”
Section: Discussionmentioning
confidence: 95%